Efficacy and safety of single high-dose versus double high-dose intracoronary bolus tirofiban in patients with ST-segment elevation myocardial infarction - Kaplan, Mehmet; Kurt, İbrahim Halil; Quısı, Alaa; Alıcı, Gökhan; Demir, Şerafettin; Yavuz, Fethi; Dönmez, Yurdaer (The European Research Journal, 2021)
Objectives: We evaluated the efficacy and safety of single high-dose versus double high-dose intracoronary bolus tirofiban in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI).Methods: A total of 80 patients, who were admitted to our clinic and underwent primary PCI, were included in this observational cohort study. The patients were divided into the single high-dose group (n = 40) and the double high-dose group (n = 40) according to the intracoronary bolus tirofiban regime. The primary endpoint was assumed as the incidence of major adverse cardiac event (s) (MACE) defined as all-cause mortality and repeat coronary revascularization (target vessel revascularization [TVR]) at 30 days. MACE and bleeding events were evaluated at 7 and 30 days.Results: The primary endpoint was not significantly different between the single and the double high-dose groups (40.0% vs. 17.5%, p = 0.994). However, a significantly lower 30-day TVR rate was observed in the double high-dose group (27.5% vs. 7.5%, p = 0.019). No significant difference was observed in terms of 30-day all-cause mortality between the two groups (12.5% vs. 10.0%, p = 0.712). Major bleeding events were not observed in any group. Multivariate logistic regression analysis demonstrated that CRUSADE score (Hazard ratio [HR]: 5.721; 95% CI: 2.036 to 16.073, p = 0.001) and platelet count (HR: 1.009; 95% CI: 1.000 to 1.018, p = 0.048) were the independent predictors of bleeding at 7 days.Conclusions: Double high-dose intracoronary bolus tirofiban in STEMI patients undergoing primary PCI was associated with significantly lower 30-day TVR rates without an increase in bleeding events. However, it did not significantly affect MACE and all-cause mortality rates.